2019
DOI: 10.1248/bpb.b19-00154
|View full text |Cite
|
Sign up to set email alerts
|

Coefficient of Determination between Estimated and Measured Renal Function in Japanese Patients with Sarcopenia May Be Improved by Adjusting for Muscle Mass and Sex: A Prospective Study

Abstract: Creatinine (Cr) levels are strongly affected by muscle mass, and the estimated glomerular filtration rate (eGFR), a measure based on serum creatinine (SCr), is often overestimated in patients with sarcopenia. To evaluate the coefficient of determination (R 2) between eGFR and the actual measured value, we performed a linear regression analysis of a modified GFR (mGFR: measured Cr clearance 0.715) and various renal function estimates adjusted for muscle mass in 19 patients with sarcopenia. The eGFR values based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…However, SCr level is strongly affected by muscle mass, leading to overestimation of kidney function in elderly sarcopenic patients. 10) In this study, there was a significant correlation between AUC REF and AUC eGFR/0.789 (p < 0.001) where AUC eGFR/0.789 tended to be lower in relation to AUC REF (Fig. 1).…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…However, SCr level is strongly affected by muscle mass, leading to overestimation of kidney function in elderly sarcopenic patients. 10) In this study, there was a significant correlation between AUC REF and AUC eGFR/0.789 (p < 0.001) where AUC eGFR/0.789 tended to be lower in relation to AUC REF (Fig. 1).…”
Section: Discussionsupporting
confidence: 49%
“…Therefore, we recommend against using eGFR/0.789 equations while planning the administration of VCM in such patients. Nakatani et al 10) reported that the prediction accuracy of kidney function could be improved by considering the muscle mass in the eGFR equation. Accordingly, further studies are needed to determine whether the Bayesian approach using the eGFR/0.789, which considers muscle mass, can improve the prediction accuracy for the AUC.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations